Gender stereotyping in FM radio stations in Iloilo City - Babiera, Debbie Rhea
Gender stereotyping has been an issue for a long period of time, but sad to say that until now, there are still limited number of people who fully understand about the issue and even few are aware that issues such gender exist. This study know if gender stereotyping exist in FM radio stations in Iloilo City. Although there are many speculations that broadcast industry is a male dominated industry, this study investigated further to have a factual data about this issue. Does gender stereotyping really exist in FM radio stations in Iloilo City? This question was answered by this study through a one-shot survey design from six different stations in the city. The selection of the respondents was through simple random method which means that, only those who are willing to answer the questions become our respondents. This study caters to those who are willing to enter in the industry and have ambitions to become a radio practitioners someday. As this study progressed the researchers find out that as a whole media industry in Iloilo city was male dominated based from the survey that was conducted from the different FM stations in Iloilo City.